Running man a memoir of ultra-endurance - Engle, Charlie 1962- (Scribner, 2017)
Ultra-marathon runner Charlie Engle chronicles his globe-spanning races, his record-breaking run across the Sahara Desert, and how running helped him overcome drug addiction ... and an unjust stint in federal prison.--Source other than Library of Congress.